Nurses facing the environment and rural workers exposed to pesticides (Research, Society and Development, 2021)
The objective is to identify the role of nurses facing rural workers and the environment exposed to pesticides between 2010 and 2020. This is a qualitative research of integrative review in 13 articles found in selected databases. There were 13 articles that met the inclusion criteria. The results indicate that the agrochemicals in small or moderate amounts contaminate soil, water and living beings, causing infection that must be notified by health professionals to SINAN, offers the Health Surveillance subsidies to care for the environment. By understanding the relationship between rural workers, the environment and pesticides, nurses can visit the socio-environmental object, interacting with the worker (subject), the environment (work space) and pesticides (work tool). We conclude that nurses are fundamental in all areas of health care for rural workers and their families, especially in the promotion and prevention of diseases caused by the use of agrochemicals.